Basic electric circuit analysis - Johnson, David E.; Zobrist, Bill.; Hilburn, John L.; Scott, Peter D. ([S.l.] : Wiley, 1995)
* Key equations are followed by a brief explanation to increase student comprehension of important mathematical concepts. * Modern op amp is presented as a versatile linear circuit element. * Highly motivational use of op amps with SPICE for exploratory active circuit design. * SPICE tutorial material placed in clearly marked sections that can be skipped or de-emphasized. No reliance on SPICE or other computer methods in the remaining sections. * Balanced emphasis given to the complementary time, phasor, and domain approaches which are the core of modern linear circuit analysis.